The Influence Of Socio-Demographic And Fp Services On Pus Participation In Fp In Kuta Raja Area, Banda Aceh City Year 2021 - Ristika Julianty Singarimbun (Sean Institute, 2021)
Indonesia is a developing country and cannot escape population problems. The main population problems faced by Indonesia are a large population with a relatively high population growth rate, unequal population distribution, a young age structure, and the quality of the population that must be improved. The sampling technique was purposive sampling with the following sample criteria: Couples of Reproductive Age (women) aged 20-35 years, Couples of Reproductive Age who have 2 children, Couples of Reproductive Age who are not pregnant or sick, the sample in this study was 83 people. The results of statistical tests using the Chi-Square test showed that there was a significant relationship between the number of children and family planning participation in Kuta Raja District, Banda Aceh City in 2021, with a value of P = 0.000 (P <0.05). The results of the analysis of the relationship between the number of children and family planning participation, of the 38 people (45.8%) who had children 0-1, there were 18 people (21.7%) who stated that they took part in family planning, this was because the respondents wanted to set the distance between the first child with the next child. Meanwhile, of the 45 people (54.2%) who had ≥ 2 children, there were 2 people (2.4%) who stated that they did not participate in family planning.